rac-Dichlorido(1-{(diphenylphosphanyl)[2-(diphenylphosphanyl)phenyl]methyl}ferrocene-κ(2) P,P′)palladium(II) dimethyl sulfoxide disolvate - Schuecker, Raffael (International Union of Crystallography, 2011)
The racemic title compound, [FePdCl(2)(C(5)H(5))(C(36)H(29)P(2))]·2(CH(3))(2)SO, features a Pd-chelating 1,3-diphosphine, which is substituted at a P-bearing asymmetric C atom by a ferrocenyl group. The Pd(II) atom is in a distorted quadratic coordination by two P and two Cl atoms with bond lengths of 2.2414 (3) and 2.2438 (3) Å for Pd—P, and 2.3452 (3) and 2.3565 (3) Å for Pd—Cl. The conformation of the Pd complex is controlled by an intramolecular slipped π–π stacking interaction between a phenyl and a cyclopentadienyl ring with corresponding C⋯C distances starting at 3.300 (2) Å and the distance between ring centroids being 3.674 (2) Å. The crystal structure is stabilized by C—H⋯Cl and C—H⋯O hydrogen bonds. The (CH(3))(2)SO solvent molecules are arranged in layers parallel to (101) and are linked in pairs by C—H⋯O interactions. One (CH(3))(2)SO molecule is orientationally disordered [occupancy ratio 0.8766 (17):0.1234 (17)] with sulfur in two positions at both sides of its C(2)O triangle.